Kondisi Psikologis Tokoh Miyaichi Kazuki dalam Kehidupan Remajanya (Kajian Psikologi Sastra pada Film Hotto Roodo) - Rahmah, Yuliani; Masitoh, Masitoh (Vocational College of Diponegoro University, 2024)
This research aims to describe the impact of inner pressure experienced by the main character Miyaichi Kazuki on his teenage life in the Hotto Roodo movie in terms of Abraham Maslow's hierarchy of needs theory. This research is included in the literature study. The method used in this research is literary sociology. The method used in this research is literary sociology because the formal object in this research is related to the psychological aspects of the character. The theory used in this research are narrative structure theory and Abraham Maslow's hierarchy of needs theory to analyze the impact of inner pressure experienced by the main character Miyaichi Kazuki on her teenage life in the Hotto Roodo movie by director Takahiro Miki. Based on the analysis of the process of fulfilling basic human needs in Kazuki's teenage life, the author finds that there is one basic human need that has been relatively fulfilled in Kazuki's life, namely physiological needs. Then the other four levels of needs appear to be unfulfilled in Kazuki's life. The unfulfillment of basic human needs in Kazuki's life led to various feelings that eventually caused mental distress for Kazuki's character. The effects of inner pressure experienced by the main character Miyaichi Kazuki in his teenage life in the film Hotto Roodo by director Takahiro Miki include fear, easily offended, insecure, depression, and physical and mental exhaustion.